OTOMASI BAHAN PUSTAKA DI PERPUSTAKAAN TAMAN KANAK-KANAK - Fadhilah Hartary Barkah; Evi Nursanti Rukmana; Asep Saeful Rohman (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
The main function of library automation is cataloging which can assist in various processes from creation, updating, copying, retrieval and record management. Library collection activities are one form of processing library collections. In this study, the main focus is on the process of automation of library materials for the Pertiwi 1 Kindergarten library using the c application. In addition, the author also describes the condition of the Pertiwi 1 Kindergarten library and also the use of the library for the development of the Pertiwi 1 Kindergarten children's reading interest. The research method used in this article is a descriptive qualitative method and the data collection techniques used are interviews and literature studies.